Impact of biofilm resuspension on mesozooplankton in a shallow coastal ecosystem characterized by a bare intertidal mudflat. (29th April 2016) - David, Valérie; Hartmann, Hans; Barnett, Alexandre; Bréret, Martine; Montanié, Hélène; Orvain, Francis; Dupuy, Christine
Abstract : A prey–predator experimental setup was conducted in a shallow coastal ecosystem characterized by a bare intertidal mudflat to test if benthic biofilm resuspension causing microalgae inputs and carbon export toward nanoflagellates would favour the highest planktonic trophic level (i.e. mesozooplankton) when nutrient concentrations are high in the water column. Mesozooplankton predation and somatic production were studied by comparing the evolution of the prey assemblage (diversity and abundances) in the presence and absence of these predators during 24 h experiments. The results were then statistically analysed according to the cross-calculation method. Biofilm resuspension caused (i) a direct input of benthic microorganisms that had changed prey structure in term of diversity and/or size and (ii) a differential growth ability between prey taxa. Both reasons implied a bottom-up control on both micro- and mesozooplankton. The carbon export toward heterotrophic nanoflagellates favoured pelagic ciliate growth while mesozooplankton benefited from largest diatoms with high growth rates, both benthic and R-strategist pelagic species. Even if these microbial and herbivorous pathways are controlled by benthic inputs, they seemed to be totally disconnected since ciliates represented only a small part of mesozooplankton diet. The sensitivity of mesozooplankton production appeared species-dependent with the most tolerant taxa dominating the zooplankton assemblages. This suggests a role of the intensities and the frequencies of biofilm resuspension on the spatio-temporal structuring of mesozooplankton in macrotidal coastal ecosystems.